ACTIVITY-BASED COST MANAGEMENT IN THE BANKING SECTOR - van der Walt, Petrus Stefanus (My University, 2011)
The South African banking sector is characterised as being highly competitive and has adopted several management accounting techniques to assist in setting the direction for the sector. As a consequence, activity-based costing (ABC) is one of the techniques employed. The research evaluated the appropriateness of ABC in the banking sector. Champions and users of ABC in the four major banks of South Africa were interviewed together with implementation consultants. The research found that ABC has particular value in the application of internal transfer pricing. The internal focus of transfer pricing raise some concern on the external value added by ABC. Differing views exist on further application of ABC. As far as implementation goes, all banks have implemented ABC with varying degrees of success. One of the major considerations that surfaced is the level of ownership by the business and continuous maintenance of the ABC system.
MBA thesis - WBS
Keywords: Activity-based cost accounting; Banks and banking